Recommendations for obtaining reliable results of resistance of concrete cylinders - González Beltrán, Guillermo (2025)
This paper is about a series of recommendations to assure the reliability of concrete strength results sampled in the field. Each of the steps to achieve this goal is described. Those are: sampling, molding, curing, protecting and testing. The provided recommendations are based on a deep study of the practices and standards as well as the experience acquired in the process of testing concrete cylinders at LanammeUCR. This paper is intended mainly for testing laboratories which execute sampling and testing of concrete but also for engineers and professionals that work in the construction of buildings.